(untitled) (Culturas Científicas, 2026)
In recent years there has been marked interest in so-called superdeterminism: the idea of evading Bell’s theorem and its consequences by denying the assumption of Settings Independence (SI). I argue that much of it is misdirected, resting on clear and well-documented misunderstandings that a straightforward review of the dispute and relevant literature would readily dispel. As a possible explanation for the growing interest in superdeterminism despite these misunderstandings, I point to a tendency among some philosophers of science to defer excessively to physicists’ conclusions and opinions. Finally, I argue that if philosophy of physics is to be useful to physics and to science more broadly—by offering conceptual clarity, identifying problems, providing constructive criticism, and guiding theory choice—it must avoid such complacency.